A Survey of the Non-flying Small Mammals at Several Elevations in and around the Crocker Range Park - Crocker Range Scientific Expedition 2002 - Henry Bernard; Kalsum Mohd Yusah; Shigeki Yasuma; Lucy Kimsui (Universiti Malaysia Sabah, 2004)
A survey was conducted on the non-flying small mammals (<1kg) at three elevations (500 m, 1000 m, and 1400 m above sea level) inside Crocker Range Park and one elevation (100 m above sea level) outside Crocker Range Park. The purpose was to document several aspects of the small mammal community structure at these elevations. The variations in habitat structure and habitat-use patterns of the small mammals are described to explain the observed differences in the small mammal community structure across different elevations. Total trapping effort was 1080 trap-nights with 106 individuals of small mammals comprising 14 species and five families caught at all elevations. One murid rodent, Niviventer rapit, caught at 1400m, is a new record for Crocker Range Park.